Antenatal Education with Booklet Media on Knowledge and Readiness of Pregnant Women under the Age of 20 Years - Ni Putu Karunia Ekayani; Nurmayasari Nurmayasari; Intan Gumilang (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2020)
West Nusa Tenggara Province is one of the areas with high early marriage cases in Indonesia. Pregnancy of women aged 10-19 years who had been pregnant reached 58.8% and currently pregnant 25.2%. The objective of this study is to determine the effect of antenatal education with the booklet media on the knowledge and readiness of pregnant women under the age of 20 in dealing with pregnancy. This research is a quasi-experiment with one group pretest-posttest. This research was conducted in May-June 2019. The population in this study was pregnant women under the age of 20 years. The sampling technique in this study was total sampling with a sample of 30 pregnant women. The analysis used the Wilcoxon Sign Rank Test and Paired Sample T-Test. The results showed that respondents in this study were 16-19 years old with the majority of secondary education and all working as housewives. There was an increase in the value of the level of knowledge and readiness from before and after the intervention was given. Statistical test results on the level of knowledge and readiness obtained p-value = 0.000 before and after given the intervention, showing the influence of antenatal education on the knowledge and readiness of pregnant women under 20 years of age in dealing with pregnancy. Future studies are expected to add to larger sample size and add other relevant variables related to pregnancies under the age of 20 years.